Factores de riesgo que desencadenan hipoacusia en los recién nacidos en el “Hospital provincial General Docente de Riobamba” periodo octubre 2016- octubre 2017 - Rodríguez Herrera, Dennis (2018)
Introduction: Neonatal is a test Auditory screening in neonates which is evaluated to establish the hearing impairment. The aim of this work is to identify the factors that trigger the hearing loss in neonates. Method: The present research is descriptive, cross-sectional and retrospective, in which 3533 stories of pregnant women were investigated. The factors were: Family history, personal pathological, use of medications in pregnancy. The data were analyzed through the statistical review in the department of statistics and audiology service in the period set. Results and conclusions: In the study group it was possible to determine that in family history the indicator with the highest prevalence is the consanguinity of the couple, which represents 48.3%. Of the personal history as a risk factor, the TORCH syndrome is predominant with 15.91%